2004
DOI: 10.1590/s1519-566x2004000300018
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Calliphoridae (Insecta: Diptera) in Hudson, Argentina

Abstract: Diversidade de Calliphoridae (Insecta: Diptera) em Hudson, Argentina RESUMO -As moscas Calliphoridae têm a importância sanitária e forense, e níveis diferentes de associação com os ambientes humanos (sinantropia). Conseqüentemente, as variações da diversidade específica em cada área poderiam ser usadas como um indicador do impacto antrópico. Neste estudo, a comunidade de Calliphoridae em Hudson (Argentina) foi coletada em três areas com graus diferentes de Sinantropia (natural, rural e urbana). As moscas foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
0
27
0
3
Order By: Relevance
“…D'Almeida and Lopes (1983) and Guimarães (2006) considered it to be an asynanthropic species. Centeno et al (2004) considered that the decreasing abundance of Paralucilia pseudo-lyrcea (Mello, 1969) was an indicator of human actions. This study in Argentina showed this species as an asynanthropic one, of high diversity in natural areas.…”
Section: Discussionmentioning
confidence: 99%
“…D'Almeida and Lopes (1983) and Guimarães (2006) considered it to be an asynanthropic species. Centeno et al (2004) considered that the decreasing abundance of Paralucilia pseudo-lyrcea (Mello, 1969) was an indicator of human actions. This study in Argentina showed this species as an asynanthropic one, of high diversity in natural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Some blowflies are considered a serious public health problem since certain species can cause myiasis in humans and domestic animals. Other blowflies are of great medical, veterinary, and forensic importance (Hanski and Kuusela 1980, Kuusela and Hanski 1982, Greenberg 1991, Martínez Sánchez et al 2000, Centeno et al 2002, 2004, Agrawal et al 2010, Davydov 2011). Calliphorids are recognized as the first wave of faunal succession on human cadavers (Nuorteva 1977, Smith 1986) and, therefore, are the primary and most accurate indicators of the time of death (Centeno et al 2002, Ames and Turner 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Eusynanthropic species are preferentially associated with human settlements, asynanthropic species avoid human populations, and hemisynanthropic species live in ecotones or transition zones . This classification has been primarily applied in entomology . However, data concerning anthropogenic influence on environmental filamentous fungi communities are scarce.…”
Section: Introductionmentioning
confidence: 99%